2016
DOI: 10.1097/pcc.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Steroid Use and Outcomes Following the Norwood Procedure

Abstract: Objective Data supporting the use of perioperative steroids during cardiac surgery are conflicting and most pediatric studies have been limited by small sample sizes and/or diverse cardiac diagnoses. The objective of this study was to determine if intraoperative steroid administration improved outcomes following the Norwood procedure. Design A retrospective analysis was performed on the 549 neonates who underwent a Norwood procedure in the publicly available datasets from the Pediatric Heart Network’s Single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…At the same time, this age group is exposed to CPB during a vulnerable phase of brain development13–15 and remains at highest risk of suffering neurological impairments16 due to acute brain injury occurring within the context of LCOS. Recent trials to reduce LCOS during cardiac surgery for CHD testing interventions such as steroids17 have not demonstrated consistent benefit 18. Given the adverse effects of CPB on early recovery and long-term neurodevelopment, there remains an urgent need for clinical trials evaluating novel therapies to address these problems 5…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, this age group is exposed to CPB during a vulnerable phase of brain development13–15 and remains at highest risk of suffering neurological impairments16 due to acute brain injury occurring within the context of LCOS. Recent trials to reduce LCOS during cardiac surgery for CHD testing interventions such as steroids17 have not demonstrated consistent benefit 18. Given the adverse effects of CPB on early recovery and long-term neurodevelopment, there remains an urgent need for clinical trials evaluating novel therapies to address these problems 5…”
Section: Introductionmentioning
confidence: 99%
“…In the neonate subgroup analyses, no difference in clinical outcomes was detected. Using datasets from a clinical trial (the Pediatric Heart Network's Single Ventricle Reconstruction trial), on neonates that had the Norwood procedure, Elhoff et al [ 47 ] compared the effect of intraoperative corticosteroid administration in 498 recipients with 51 non-recipients and found in the multivariate analysis no effect of corticosteroid on lengths of stay but a trend toward better hospital survival in non-recipients. This is one of the few studies where the authors have also looked at the neurodevelopment outcomes at 14 months and found no difference.…”
Section: Resultsmentioning
confidence: 99%
“…Our results harmonize with a recent study of intraoperative steroid use during the Norwood in the SVR Trial, in which intraoperative steroids were associated with greater hospital mortality in a multivariable logistic regression. 39 In a meta-analysis including 232 patients, intraoperative steroid use was not associated with significant reductions in morbidity or mortality in children undergoing cardiac surgery. 40 However, other published studies from the last decade present contradictory results.…”
Section: Discussionmentioning
confidence: 97%